2017
DOI: 10.1007/s11661-017-4134-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the Fe-Mo-Ti Ternary System at 1173 K (900 °C) and 1023 K (750 °C)

Abstract: Alloys with fine-scale eutectic microstructures comprising Ti-based A2 and TiFe B2 phases have been shown to have excellent mechanical properties. In this study, the potential of alloys with further refined A2-B2 microstructures formed through solid-state precipitation has been explored by analyzing a series of six alloys within the Fe-Mo-Ti ternary system. Partial isothermal sections of this system at 1173 K (900°C) and 1023 K (750°C) were constructed, from which the ternary solubility limits of the A2 (Ti, M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(37 reference statements)
1
3
0
1
Order By: Relevance
“…The streaking of the ω reflections indicates a structure change between the conditions, which may also influence their intensity [27]. High-angle annular dark-field (HAADF)-STEM imaging in the aged condition, Figure 1d, indicated that the B2 precipitates had similar Ti content but were enriched in Fe and contained minimal Mo, Figures 1e and f. This was consistent with near equilibrium compositions at 750 • C of (62.8±0.6)Ti -(6.4±0.4)Fe -(30.8±1.0)Mo (at.%) for A2 (Ti, Fe) and (52.4 ± 0.6)Ti -(44.6 ± 1)Fe -(2.9 ± 1.0)Mo for B2 TiFe [20]. The reduction in Fe and enrichment in Mo of the bcc (A2) matrix could be expected to lower the propensity for ω formation [13,27], as observed.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…The streaking of the ω reflections indicates a structure change between the conditions, which may also influence their intensity [27]. High-angle annular dark-field (HAADF)-STEM imaging in the aged condition, Figure 1d, indicated that the B2 precipitates had similar Ti content but were enriched in Fe and contained minimal Mo, Figures 1e and f. This was consistent with near equilibrium compositions at 750 • C of (62.8±0.6)Ti -(6.4±0.4)Fe -(30.8±1.0)Mo (at.%) for A2 (Ti, Fe) and (52.4 ± 0.6)Ti -(44.6 ± 1)Fe -(2.9 ± 1.0)Mo for B2 TiFe [20]. The reduction in Fe and enrichment in Mo of the bcc (A2) matrix could be expected to lower the propensity for ω formation [13,27], as observed.…”
supporting
confidence: 85%
“…Studies have been made on phase equilibria in the ternary Ti-Fe-Mo system [16][17][18], with recent work demonstrating that A2+B2 microstructures could be formed, which have high hardness, but also possessed an unavoidable micron scale intermetallic phase [19]. From the solvus position determined in previous studies [19,20] a new alloy has been designed that can be solution heat treated within the A2 single-phase field and subsequently aged at a lower temperature to form B2 precipitates within the A2 Ti matrix. Here, the microstructure of this new alloy with composition Ti-17Fe-23Mo (at%) is discussed and its mechanical behaviour examined.…”
mentioning
confidence: 99%
“…According to Knowles et al, molybdenum is only slightly soluble in FeTi, replacing titanium up to 2 at. % at 1173 K [40].…”
Section: Fetimentioning
confidence: 98%
“…%), at least in the 1173-1273 K temperature range [39]. Molybdenum can fully substitute titanium between 1023 and 1173 K [40].…”
Section: Fe 2 Timentioning
confidence: 99%
“…A fase com estrutura cristalina C14 (a = 0,481 nm; c = 0,791 nm) apresentou a seguinte quantificação EDS (em %atômica): Fe = 63,4%; Ti = 31,4% e Mo = 5,2%, evidenciando mais uma vez a ocorrência de solução sólida entre Fe2Mo e Fe2Ti. [87][88][89] Figura 22 -Secção isotérmica calculada do diagrama Fe-Mo-Ti a 850 ºC mostrando a variação de composições (Mo e Ti) para teor de ferro constante (seta em vermelho)…”
Section: Fe-18ni-5mounclassified